Editorial, Volume 10 (2019) - Shaaban, Muhammad (JOURNAL OF ADVANCES IN AGRICULTURE, 2019)
On behalf of the Editorial Board, it is with great pride and sincere privilege that I am writing this message to present the volume 10 (2019) of the JOURNAL OF ADVANCES IN AGRICULTURE. The issue comes from a long process, and we took all the necessary steps to make it a high-caliber scientific publication. We are relying on the collaboration of all our Editors, reviewers, and contributors to make it a contemporary, lively, and relevant publication.